Model for estimating the linear electron density of the trail created by a meteoroid - Holovan, O.V.; Kharchenko, V.M. (Radiotekhnika, 2024)
An assessment of the linear electron density of the trail (LEDTr) created by a meteoroid when passing through the Earth's atmosphere at a given observation altitude is used to calculate the power of the received radio signal and predict the reflectivity of the trail in the process of its further transformation. In the published works, the formulas for calculating the LEDTr do not show its relation to altitude, and there are no explicitly specified parameters of the meteoroid body and atmosphere. When developing the presented model for estimating LEDTr, the main physical processes occurring during the interaction of a meteoroid with atoms and molecules of the atmosphere were taken into account. The proposed calculation of the LEDTr includes an assessment of the midsection of the meteoroid's head, the concentration of particles (numerical density) in the atmosphere, and the value of the integral ionization coefficient at the observation altitude. The necessary calculation formulas were obtained, and a software-implemented calculation algorithm was presented. Unlike to the well-known formulas for calculating LEDTr and semi-empirical models obtained by fitting to the results of radar observations, the presented technique allows calculations to be carried out for explicitly specified parameters of the meteoric body and atmosphere. It is important to note that when estimating the mass loss of the meteoroid, a recurrent method was used to calculate the mass and velocity as its altitude changed. This method made it possible to take into account changes in the mass and midsection of the meteoroid during its movement. The obtained relation of LEDTr to altitude corresponds well to the luminosity curves of the meteor trail, and the value of the electron density at the ionization maximum corresponds to the known observational results. Estimating the LEDTr for a given (measured) reflection point makes it possible to calculate the amplitude-time characteristics (ATCH) of radio signals, which allows for the creation of a model image of a scattered signal. Comparison of the ATCH of the received signal with the calculated model images allows one to make informed assumptions about the characteristics of the meteoroid that generated the ionized trail.